Six new species of Nesocordulia McLachlan, 1882 reveal an insular evolutionary radiation of dragonflies on Madagascar (Odonata: Anisoptera: Libelluloidea) - Bernard, Rafał; Daraż, Bogusław; Ravelomanana, Andrianjaka; Dijkstra, Klaas-Douwe B. (Zootaxa, 2025)
Nesocordulia McLachlan, 1882 is a poorly known dragonfly genus endemic to Madagascar and the Comoros. The genus is revised, and all twelve species are described, including six new ones: N. coloratissima sp. nov., N. evanida sp. nov., N. fossa sp. nov., N. ipsio sp. nov., N. lyricauda sp. nov., and N. odonator sp. nov. All are well-defined, with notably distinct male cerci, hamules, and colouration. While an identification key for males of all species is provided, this is based on single specimens for six of them. Females are known for only six species. While several radiations of damselfly genera had been recognised in the Malagasy Region already, Nesocordulia is the first to be uncovered in the suborder Anisoptera. Due to the scarcity of data, the exact drivers of their diversification remain unclear, however. While seven species are known from the humid and subhumid forest zone of eastern and north-western Madagascar, and only N. coloratissima and N. villiersi Legrand, 1984 appear confined to the drier west and to the Comoros respectively, the exact collection localities of three species remain unknown. Although the limited data suggest that most species are localised, the few species with more records appear to be fairly widespread. The species’ ecology is almost unknown, with more details provided on the habitat and behaviour of N. evanida only, and their conservation status is also largely unknown. Four species have not been recorded for over a century, however, while only N. coloratissima and N. evanida were confirmed to inhabit anthropogenically influenced landscapes.